STUDI KOMPUTASI BERBASIS DFT TERHADAP FENOMENA QUANTUM TUNNELING DALAM ISOMERISASI METILHIDROKSIKARBENA - Jumaidil Awal; Rahmat Gunawan; Eva Marliana (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2012)
Density functional theory-based methods have been applied to predict the most possible one among the isomerizations of methylhydroxycarbene considering the probability of hydrogen tunneling occurrence. B3LYP/6-31+G(d,p) and M08-SO/6-31+G(d,p) methods were applied in all computations using GAMESS-US software. There were three steps of computation in this research. First, electronic structure computations of both equilibrium and transition compounds involved in all isomerization alternatives in order to obtain the optimum structures of the compounds. Second, vibrational computations of optimum transition structures to ensure that each of the respective structures is well on its potential energy surface. Third, tunneling analysis accomplished by intrinsic reaction coordinate (IRC) computatuins for all isomerization alternatives followed by tunneling probabilitycalculation using the Wentzel-Kramers-Brillouin (WKB) formula for methylhydroxycarbene isomerizations. The result of this research showed that the DFT methods successfully produced the optimum structure of each compound. Both DFT methods also successfully mapped all the intrinsic reaction coordinates. B3LYP/6-31+G(d,p) method gave tunneling probabilities of 3.55 x 10-19 for the isomerization into acetaldehyde and 3.30 x 10-20 for that into vinyl alcohol. While M08-SO/6-31+G(d,p) method gave tunneling probabilities of 2.38 x 10-23 for the isomerization into acetaldehyde and 4.79 x 10-23 for that into vinyl alcohol.Keywords: DFT, methylhydroxycarbene, hydrogen tunneling, isomerization